Boat green : 50 steps boaters can take to save our waters - Ford, Clyde W. (desLibris. Books collection., 2008)
Boat Green provides a host of environmentally sound boating practices, based on scientific research and practical boating experience. In this book, boaters will learn ways to: reduce vessel operation and maintenance costs, improve vessel performance, increase safety and health of vessel operators and crew, increase awareness of marine issues and enhance enjoyment of the marine environment. All of these steps will help lessen the impact of recreational boating on the marine environment.